The Circulation of Icons in Planetary - Pictures, Popular Culture and Materiality - Nicolas LABARRE; Laura PERNA; Errol RIVERA (E-REA)
Planetary, a comic book series published in the United States between 1999 and 2009, provides a striking example of the use of intericonicity as a structuring device in an erudite popular culture opus. In the series, the readers and the protagonists are invited to explore the “secret” history of a fictional world. This history is composed of visual allusions to notable works of 20th-century popular culture. The main character in the story is an amnesiac who rediscovers this buried history—seeing the images anew, yet knowing he has experienced them before—a device which allows the trajectory of the narrative and the experience of the reader to coincide. This article seeks to analyze the way Planetary uses the metaphor of archeology to make the circulation of these images possible: each icon is turned into an artifact in the diegetic world, which is investigated by the protagonists until its meaning is re-created, leading to a reactivation of the icons through a process of defamiliarization. Planetary offers a readerly contract akin to those of the “metafictions” described by Patricia Waugh, but transposes this contract into a primarily visual form. This leads to the development of various strategies, including the creation of a “master style”, a specific visual idiom into which the various icons are translated.